Academic Writing Using Critical Thinking Approach of Student PBSI FBS Universitas Negeri Yogyakarta - Setyawan Pujiono (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The main problem in this article is the low awareness of students' critical thinking when writing various academic activities. One of the reasons for this condition is that learning to write academic forms has not used the right approach or model. The purpose of writing this article is to describe the application of Critical Thinking in student academic writing. This research was written using literature study and direct observation of the academic writing lecture process, namely writing scientific papers. The results of the observation show that in a class that does not use the Critical Thinking approach, it shows that during the academic writing lecture process, students have not developed the concept of critical thinking properly so that their written work has not produced critical and innovative products. However, in classes that apply the Critical Thinking Approach, lectures have been running effectively and the students' written work is in accordance with the assessment criteria. This increase and effectiveness is because students carry out the stages of analysis, evaluation, reconstruction, and creativity during writing lectures.